cidesd 2014 - International Congress of exercise and sports performance (Polytechnic Institute of Guarda, 2014)
aus dem Inhalt: - Understanding offensive patterns of performance of futsal top level national teams - Footballers' movement behaviour when playing small-sided games manipulating the number of opponents and teammates - The influence of early sport involvement in a basketball enrichment training program - Performance and variability profiles in competition of nba players: comparing between all-star and non-all-star players - Typical weekly workload of under-15, under-17 and under-19 elite portuguese football players - Effects of using balls from other sports on external workload of players during football small-sided games - The effect of team timeout on the performance indicators in handball match according to the competitive context - Quantitative analysis of leader-follower interactions between football players - Effects of goal manipulation and age level on players performance in futsal - The changing rule effect on basketball performance - Individual and collective creativity in young footballers - The acquisition of aquatic skills in preschool children varies according to the water deep environment during swimming lessons - Physical and tactical performance of elite footballers during the preseason - Soccer analysis of the international milan long term attack that end successfully - How game phase affects the type of set used by u19, u21 and senior male beach volleyball players - Team performance according to ball possession characteristics: a social networks approach - The effect of performance indicators on the time of the first goal scoring in the football match - Time-motion analysis in youth elite rugby players during game training - Game analysis in the era of big data: a social networks approach - Effect of training and exercise intensity on indices of oxidative balance - Infants' physiological response to four months of a swimming program - Modeling performance and biomechanics in young swimmers - Magnesium and phase angle: a prognostic tool in cellular integrity of judo athletes - 2000m all-out and time sustained at 100% of vo2max intensity in rowing ergometer exercise - Post warm-up recovery and performance in swimming - Reliability and construct validity of yo-yo intermittent tests in untrained and football trained pupils - Excellence in orienteering: representation from elite coaches - Seasonal adaptations in the physical performance of futsal players and its effects on defensive skills - The effect of the application of a physical fitness program before and after technical/tactical work in team sports in physical education - Influence of strength, sprint running, and combined strength and sprint running training on short sprint performance in young adults - Power assessment in young male soccer goalkeepers: variation by competitive level - Electromyography in swimming performance: a review - Assessment of anaerobic performance in young swimmers using laboratory and sport specific tests - Cortisol, testosterone and mood state variation during an official female football competition - Anaerobic energy release during various resistance exercises performed at 80% 1-rm - Maximal oxygen uptake in professional football players: comparison between levels and playing positions - Comparison of the hamstring/quadriceps ratios for the assessment of muscle balance in football players of first and second portuguese leagues - Football analysis of the international milan long term attack that end successfully - Post-activation potentiation after a conditional contraction - Sport trajectories and involvement of portuguese olympic rising stars - Spatio-temporal coordination in front crawl at different intensities - a case study - Energy system contribution during 100 m front crawl swimming - The effect of diferent warm-up in handball: termography analysis - Flexibility methods effect in explosive strength in gymnastics/teamgym